Latitudinal variation in plant defence against herbivory in a marine foundation species does not follow a linear pattern: The importance of resource availability. Issue 1 (17th November 2020) - Hernán, Gema; Ortega, María J.; Henderson, Jeremy; Alós, Josep; Boyer, Katharyn; Cimon, Stephanie; Combes, Vincent; Cusson, Mathieu; Hereu, Clara M.; Hessing‐Lewis, Margot; Hovel, Kevin; Jorgensen, Pablo; et al.
Abstract: Aim: Studies on latitudinal patterns in plant defence have traditionally overlooked the potential effect that resource availability may have in shaping plant defence. Likewise, latitudinal patterns of tolerance traits have rarely been studied, yet they can be a critical component of plant defence. Therefore, the aim of our study was to examine latitudinal variation in the production of tolerance and resistance traits against herbivory along a latitudinal range and a natural gradient of resource availability from upwelling conditions. Location: North America (Canada, USA, Mexico). Time period: Summer months of 2015. Major taxa used: The seagrass Zostera marina . Methods: We conducted experiments simulating macroherbivore (e.g., bird, fish) damage on the seagrass Z. marina at 10 sites across the Eastern Pacific coast (Canada–Mexico) and Quebec and analysed several traits related to resistance and tolerance strategies against herbivory. In addition, we examined the effects of potential seagrass changes in defence strategies by performing a series of feeding experiments with mesoherbivores in a subset of sites. Results: We found that eelgrass resistance defences did not follow a linear latitudinal pattern but rather followed a bell‐shaped curve which correlated with bottom‐up control. In sites with higher nutrient availability, plants allocated resources to tolerance strategies and had lower resistance traits. Furthermore, seagrasses did not respond linearly to increased herbivory pressure; while they tolerated moderate levels of herbivory, they underwent a significant reduction in tolerance and resistance under high herbivory levels, which also made them more susceptible to consumers in feeding experiments. Main conclusions: Our results highlight the importance that nutrient availability has in shaping latitudinal patterns of plant defence against herbivory and show how these defences may not respond linearly to increased herbivory pressure in seagrasses.